Karate: Emotions and movement anticipation - Contiero, D.; Kosiewicz, J.; Baker, J. S. (Physical Culture and Sport. Studies and Research, 2018)
The following paper is a case study developed to investigate the possible relationship between mirror neurons and karate. In karate, athletes are often trained to anticipate the opponent`s movement and to consider their emotions (Dosil 2006). This kind of training and skill may be linked to the concept related to mirror neurons, which are connected to the identification of the intention behind an action and are involved in a sort of automatic empathy of "really feeling what another person is feeling or going to do" (Carey 2006). Methods The research is an introductive literary review about martial arts and the theory of mirror neurons and provides a case study based on interviews. Participants have been asked to answer five questions related to the topic. All of them are expert athletes at the black belt level or with at least 10 years of training experience.